Clonorchis sinensis-driven hepatocarcinogenesis via E2F1-CD24 transcriptional axis: mechanistic and therapeutic implications - Wen-Min Lu; Jin Yan; Zhao-Ji Liu; Yong Wu; Qian-Ru Cui; Ji Feng; Yu Chen; Guang-Zhi Zhu; Tao Peng; Jing Zhou; Guo-Dong Lu (Parasites & Vectors)
Abstract Background Hepatocellular carcinoma (HCC) remains a global health burden, with disproportionately high mortality in China’s Guangxi region, where endemic Clonorchis sinensis (C. sinensis) infection coincides with elevated HCC incidence. Preliminary single-cell sequencing revealed marked overexpression of cluster of differentiation 24 (CD24) in HCC tissues, suggesting its potential pathological role. This study aims to elucidate the oncogenic mechanisms of C. sinensis excretory-secretory products (CsESPs) and their link to CD24-mediated HCC progression. Methods We employed an integrated clinical and experimental approach. First, clinical cohort analysis assessed CD24 expression in C. sinensis-associated HCC cases. Multiplatform bioinformatics validation (GEPIA/UALCAN/TIMER) evaluated CD24’s prognostic significance and immune microenvironment modulation. Functional studies (quantitative polymerase chain reaction (qPCR), Western blotting, CCK-8 assays, flow cytometry) examined CsESPs’ effects on CD24 expression, cell proliferation, and apoptosis. Mechanistic investigations (chromatin immunoprecipitation, dual-luciferase reporter assays) identified E2F1-mediated transcriptional activation of CD24. siRNA-mediated CD24 knockdown validated its role in CsESPs-driven oncogenesis. Additionally, the expression of immune checkpoint (CTLA-4, LAG-3) was assessed in the co-cultures of peripheral blood mononuclear cells (PBMCs)–HCC cells. Results Clinical cohort analysis confirmed significant CD24 upregulation in HCC, particularly in C. sinensis-infected cases. Bioinformatic analyses linked high CD24 expression to poor prognosis and immune microenvironment alterations. Functional assays demonstrated that CsESPs enhance CD24 expression, promoting proliferation and inhibiting apoptosis. Mechanistically, E2F1 directly binds to CD24 promoter, driving its transcription upon CsESPs exposure. CD24 silencing reversed CsESPs-induced oncogenic effects. Furthermore, CsESPs upregulated immune checkpoints (CTLA-4, LAG-3) in the co-cultures of PBMC–HCC cells, an effect reversed by CD24 knockdown. Conclusions Our findings establish a novel parasitic carcinogenesis paradigm wherein C. sinensis promotes HCC development through E2F1-mediated transcriptional activation of CD24, simultaneously identifying prognostic biomarkers and therapeutic targets while suggesting combinatory immunotherapy strategies for parasite-associated HCC. Graphical Abstract